Pengaruh Kemampuan Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Kesehatan Provinsi Kalimantan Barat - B31110059, Cahyo Setiadi (Jurnal Manajemen Update, 2015)
This Thesis titled "The Effect of Work Ability and Discipline Against Employee Performance in West Kalimantan Provincial Health Department". The study variables were used in this study: 1) Ability (Knowledge, Skill, Qualification). 2) Discipline Work (Attendance, Reply Services, Justice) and 3) Performance (Loyalty, Responsibility). This research was conducted at the Employee Health Department of West Kalimantan Province. The respondents in this study are defined as 67 (sixty seven). The purpose of this study was to determine the extent of the influence of ability and discipline in West Kalimantan Provincial Health Office. In this research, the writer used descriptive and causal associative. Then the data analysis techniques using qualitative analysis and quantitative analysis to look through the questionnaire respondents, then the data were analyzed with SPSS version 17.00. Research has been done found that based on the partial test and simultaneously, it is known that factors capability consisting of knowledge, skill, qualification and discipline that consists of a list of attendees, retribution, justice significant effect on employee performance West Kalimantan Provincial Health Office. Keywords : Ability, Discipline Work, Performance